Gene–Gene Interactions Between Glutathione S-Transferase M1 and Matrix Metalloproteinases 1, 9, and 12 in Chronic Obstructive Pulmonary Disease in Serbians. (2nd November 2017) - Stankovic, Marija; Nikolic, Aleksandra; Nagorni-Obradovic, Ljudmila; Petrovic-Stanojevic, Natasa; Radojkovic, Dragica
ABSTRACT: Chronic obstructive pulmonary disease (COPD) is a complex disorder influenced by multiple genetic and environmental factors, as well as their interactions. Since elevated oxidative stress and protease activity characterize the pathogenesis of COPD, variants of genes that can affect these processes have been commonly studied in COPD. However, interactions among genes that can influence oxidative stress and protease activity remain poorly investigated in COPD. The aim of this study was to look into the role of functional variants in matrix metalloproteinases (MMPs) 1, 9, and 12 in the occurrence and/or modulation of COPD, and to analyze their interactions with glutathione S-transferases (GSTs) M1, T1, and P1 in the pathogenesis of COPD in Serbians. The MMP1 rs1799750 G > GG, MMP9 rs3918242 C > T, and MMP12 rs2276109 A > G variants were analyzed by direct detection methods. Gene–gene interactions between variants in MMPs and GSTs were assessed using a case-control model. Our results showed association of the MMP1 GG/GG genotype with COPD ( p = 0.036, OR = 2.50). Gene–gene interactions between the GSTM1 null and MMP1 GG ( p = 0.028, OR = 2.99) and the GSTM1 null and MMP12 AA variants ( p = 0.015, OR = 3.82) were found to significantly increase the risk of COPD occurrence. Furthermore, the MMP12 G variant was found to modify the age of COPD onset ( p = 0.025, OR = 3.30), while interaction between the GSTM1 null and MMP9 T variants was found to modify the severity of disease ( p = 0.019, OR = 4.83). To our best knowledge, this is the first study revealing several gene–gene interactions affecting oxidative stress and protease activity in the pathogenesis of COPD.